THE APPLICATION OF LEARNING THE BOOK OF TA'LIMUL MUTA'ALLIM TOWARD THE FORMATION OF MORAL VALUES OF SANTRI PONDOK PESANTREN DARUL HIJROH SUKOHARJO - Setiyono, Muh. Ridwan; Rohimah, Siti; Fatimah, Meti (Institut Islam Mamba'ul 'Ulum Surakarta, 2023)
Humans are the most perfect creation of Allah. Humans on this earth are caliphs, one of whose duties and mandate is to raise people from ignorance with education and moral knowledge. Moral education is an education that is very prioritized in education, it is the main goal that must be achieved. If humans do not have morals, they will lose their status with Allah as perfect and noblest creatures. In learning the book of Ta'limu Muta'alim, it is necessary to apply it in order to form moral values that should be used as guidelines and guidelines in this life. The problems raised in this study include questions: 1) How is the effect of the application of learning the Ta'limu Muta'allim Book on the formation of the moral values of the students of the Darul Hijroh Islamic boarding school. This type of research approach is qualitative. As directed by the type of qualitative research, the collected data is analyzed with intellectual weapons in the form of theories to obtain various interpretative descriptions according to logical and rational scientific research rules based on the data collected. encountered in the field using data collection techniques through observation, interviews, & documentation. By using data validity through credibility, transferability, dependability & confirmability tests. The results showed that the application of learning the Ta'limu Muta'allim Book on the formation of the moral values of the students of the Darul Hijroh Islamic boarding school, teaches the attitude of love for Allah, knowledge, and the carriers of knowledge, namely teachers. Train students patience, keistiqomahan and tawakal to Allah SWT. Self-actualization through the application of Ta'limul Muta'alim learning can be seen from the achievement of indicators regarding students' self-understanding of the nature of students regarding their moral potential. In this study, students showed good and sufficient understanding and self-direction. good and sufficient self.